(untitled) (CIPEEX, 2024)
Based on a bibliographic research, this text aims to understand the requirement of human educability. In short, it is about shedding light to answer the question: “Why do we talk about education and do we need it?”. In this sense, it is considered that the desire that this world can deepen and continue to exist, beyond the duration of a lifetime, feeds the desire to educate future generations. First, to get to know the human world and become familiar with it, it is necessary to immerse oneself in the language, learn from others and incorporate the historical and cultural legacy of previous generations. It is in this place that education is inserted, a meeting place between the old and the new. Thus, the need to preserve a heritage and take care of those who come as a novelty is formed. If it has to do with those who arrived before us in this world, it fundamentally configures the educational field, since we always educate the generations that arrive from what represents our perceptions about the desirable – inherited by the dialogue with the generations that preceded us – about the human and the human world, so that the generations understand our human condition. Taking responsibility for the common world and for the new generations is the essential task of all those who want the world to continue, last and deepen. This is, in our view, the crucial task of education, and it imposes the requirement of educability!